ANALISIS PENJADWALAN DAN ALOKASI SUMBER DAYA PADA PROYEK KONSTRUKSI MENGGUNAKAN MICROSOFT PROJECT (Studi Kasus Pekerjaan Struktur Proyek XYZ) - Danang Isnubroto; Citra Kharisma Putri (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2021)
One of the computer applications that can be used in project management control is the Microsoft Project application. With Microsoft Project , information related to activities that fall into the critical trajectory and allocation of resource placement can be known, so that the project does not experience delays and a decrease in work productivity. Based on the results of the analysis using the Microsoft project, it is found that activities are included in the critical trajectory, namely: pile work, soldier pile, excavation, excavation fireplace, brickwork installation, work floor, pile cap and superstructure work. The results of the analysis show the need for the number of workers from the 1st month to the 8th month: 31, 43, 43, 40, 37, 31, 10. The needs of the foreman are: 2, 3, 3, 2, 2, 2 , 2, 1. For crane operator resources in the 1st month and 2nd month is as many as 3 people. Subcontractor 1 and subcontractor 2 require as many as 1 person in the resources of the 2nd month to the 3rd month. A mason is needed from the 2nd to the 8th month: 12, 9, 8, 7, 7, 6, 2. Resource analysis for the head mason every month: 3, 3, 2, 2, 2, 2, 1. Analysis of the allocation of resource placement can be carried out in several stages if a graph of the resources fluctuates or does not comply with the principle of resource allocation.